Performance evaluation of a few- and multimode fiber optic perimeter sensor with selective mode excitation - Miletiev, Rosen; Arnaudov, Rumen; Bock, Wojtek J.; Eftimov, Tinko A.; Bao, Xiaoyi (Photonics Letters of Poland, 2010)
We present a study of the performance of a simple fiber-optic perimeter snsor based on selective mode excitation in few- and multimode optical fibers. The electronic unit identifies an intrusion on the basis of a pre-defined threshold and number of detected pulses per unit time. The sensor may be controlled using the keypad, a PC or a FSK modem. The statistical properties of the responses are analyzed using Weibull distributions. Full Text: PDF References: A. Yariv, "On transmission and recovery of three-dimensional image information in optical waveguides", J. Opt. Soc. Amer., 66, 301(1976) [CrossRef] A. S. Wu, S. Yin and F.T.S. Yu, "Sensing with fiber specklegrams", Appl. Opt. 30, 4468 (1991).[CrossRef] S. Yin, P. Purwosumarto and F.T.S.Yu, "Application of fiber specklegram sensor to fine angular alignment", Opt. Commun. 170, 15 (1999) [CrossRef] A. F. T.S. Yu, K.Pan, C. Uang and P.B. Ruffin, "Fiber specklegram sensing by means of an adaptive joint transform correlator ", Opt. Eng. 32, 2884 (1993). [CrossRef] F. T.S. Yu, K.Pan, D. Zhao and P.B. Ruffin, "Dynamic fiber specklegram sensing", Appl. Opt. 34, 622 (1995). [CrossRef] K.Pan, C.-M.Uang, F.Cheng and F.T.S. Yu, "Multimode fiber sensing by using mean-absolute speckle-intensity variation", Appl. Opt. 33, 2095 (1994). [CrossRef] A. Malki, R. Gafsi, L. Michel, M. Labarr?re and P. Lecoy, "Impact and vibration detection in composite materials by using intermodal interference in multimode optical fibers", Appl. Opt. 35, 5198 (1996). [CrossRef] J. Park, J. of the Korean Phys. Soc. 50, 529 (2007). [DirectLink] D. Anderson, Fiber SenSys White Paper R.Arnaudov, W. Bock, R.Miletiev, Y. Angelov and T. Eftimov, IMTC 2007, Warsaw, Poland, paper IM-7352(2007). T.Eftimov and T.Kortenski, "Mode Pattern Rottation Effect in Spirals of Multimode Optical Fibres", Bulg. J. Phys. 14, 456(1987). [DirectLink]